GAMBARAN PENERAPAN PROTOKOL KESEHATAN 3M DI MASYARAKAT PADA MASA PANDEMI COVID-19 : LITERATURE REVIEW - Prima Dewi Novalia; Lina Handayani (Dian Nuswantoro Semarang, 2021)
At the end of 2019, the world was shocked by the new virus called the corona virus (COVID-19), this virus was first discovered in the Wuhan area, China. COVID-19 is an infectious disease that attacks the respiratory tract. Humans exposed to this virus usually experience mild to severe symptoms. The purpose of this literature study is to discuss how the 3M health protocols application . the method us the literature review. The literature consists of journals with a travel year from 2011 to 2021. Literature collection is done through google scholar using the keywords “3M health protocol”, “COVID-19 pandemic”, and “community”. The results of the literature search were 73 articles that were relevant to the keywords, as many as 60 articles were excluded because they were not relevant to the author’s criteria. Total 13 articles using inclusion and exclusion criteria were obtained 5 articles with good quality. Review results show that most people have not implemented 3M health protocols properly and correctly, this is one of the causes of the increase in COVID-19 cases.